(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
The method of research that writer use in this research is quantitative research method, that is research method based on philosophy of positivism, which is used for research in certain population or sample. The sampling technique used is the saturated sample technique from the research in Inspectorate of North Halmahera District from 31 ASN. Data analysis techniques used are simple linear regression analysis and simple correlation analysis. Based on the results of analysis using product moment correlation of people obtained correlation coefficient (r) = 0.343 while the coefficient of determination (r2) = 0.34. These results show that the coefficient of determination is 34%. With this result, it can be explained that ASN performance improvement is determined by education by 34% while 65% is determined by other factors. Based on the results of the above research, the hypothesis in the post can be accepted that there is a level of relevance and determination between ASN performance educations in North Halmahera district inspectorate. Based on the significant test results obtained t = 2.280 at significant level (Î±) = 0.05 with degrees of freedom (df) = n - 2 = 29, then table = 2.045. From the data obtained that t arithmetic greater than ttable where t arithmetic 2,280> 2.045. Then H1 is accepted and HO is rejected. This proves that there is a positive influence between Education on Performance Asn in Kab. North Halmahera Based on the results of the study, it can be concluded that education has an influence on ASN performance. But in the category of calculation of interpretation of education fall into the weak category. So the better the ASN education, the better the performance will be, so it should improve the program "education both formal, informal, non formal education, in the process of achieving performance results. Keywords: Education, Performance of Civil State Apparatus,